Management of internet addiction in an 18-year-old female with endoxifen: a case report - Singh, Tanu (International Journal of Research in Medical Sciences, 2025)
Internet addiction has emerged as one of the rising health concerns in the adolescent age group in recent years, which is traditionally treated with psychotherapy. However, some patients require pharmacotherapy to manage their symptoms. This case report explores the treatment of an 18-year-old female diagnosed with internet addiction. The treatment regimen included endoxifen as adjunctive therapy alongside vilazodone, clonazepam and behavioural therapy. Over one-month period, notable improvements were observed in her symptoms, assessed through clinical global impressions and standardized internet addiction testing. The finding indicates that endoxifen, a direct protein kinase C (PKC) inhibitor, may be an effective treatment for such patients, especially those who do not respond to conventional therapies. This case report emphasizes the future studies focusing on the role of endoxifen in patients with behavioural addiction.